2019
DOI: 10.1088/1741-4326/ab312c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in situ work function and cesium flux measurement setup suitable for cesium seeded negative ion source applications

Abstract: A proof of principle experiment has been performed for the in situ measurement of the work function in vacuum conditions (~10 −7 torr) relevant to cesium-seeded negative ion sources for fusion applications. The work function is measured using the principle of the photoelectric effect. The performance of the work function measurement setup and temperature-controlled cesium (Cs) oven has been characterized using various diagnostics such as a quartz crystal microbalance, a surface ionization detector and pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is experimentally observed that optimum Cs coverage on tungsten (W) or molybdenum (Mo) surfaces can achieve very low work functions in the range of 1.4-1.6 eV [6]. During negative ion source operation, the Cs monolayer is continuously renewed, with the caesiated surfaces maintained at 150 • C to keep the work function as low as possible and preserve the balance between Cs evaporation and deposition rates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is experimentally observed that optimum Cs coverage on tungsten (W) or molybdenum (Mo) surfaces can achieve very low work functions in the range of 1.4-1.6 eV [6]. During negative ion source operation, the Cs monolayer is continuously renewed, with the caesiated surfaces maintained at 150 • C to keep the work function as low as possible and preserve the balance between Cs evaporation and deposition rates [7,8].…”
Section: Introductionmentioning
confidence: 99%